Association between circulating irisin levels and epicardial fat in patients with treatment-naïve overt hyperthyroidism. (17th November 2018) - Şahin, Mustafa; Canpolat, Asena Gökçay; Çorapçioğlu, Demet; Canpolat, Uğur; Emral, Rıfat; Uysal, Ali Rıza
Abstract: Background: Hyperthyroidism is associated with increased metabolic activity and thermogenesis. Irisin is a key molecule in thermogenesis and energy expenditure via adipose tissue browning. Epicardial fat was previously defined as brown-like fat. Thus, here we aimed to evaluate the association between serum irisin level and epicardial fat thickness (EFT) in patients with hyperthyroidism. Methods: A total of 25 hyperthyroid patients and 24 age-, sex- and BMI-matched healthy controls were enrolled. Serum irisin levels, thyroid hormone levels, and body compositions were compared. EFT was measured via transthoracic echocardiography. Results: Serum irisin level and EFT were significantly higher in the hyperthyroid group ( p  < 0.001 and p  = 0.001, respectively). The distributions of fat-free mass, muscle mass and fat mass were similar between the study groups. Serum irisin level was negatively correlated with TSH ( p  < 0.001) and positively correlated with fT3 ( p  < 0.001), fT4 ( p  < 0.001) and TSH receptor antibody ( p  = 0.002) levels and EFT ( p  = 0.001). In multivariate linear regression analysis, TSH ( β  = −0.475, p  < 0.001) and EFT ( β  = 0.290, p  = 0.023) levels were significantly associated with serum irisin levels. Conclusions: An increased serum irisin level associated with EFT might contribute to metabolic derangement in hyperthyroidism. Further studies are needed to elucidate whether irisin levels and EFT are affected by hyperthyroidism or vice versa.